Children’s Rights After Divorce under the Moroccan Family Code: Strengthening Judicial Protection in Family Court Decisions - Abdelmounaim Elmoumni (Jurnal Hukum Keluarga, 2026)
Divorce represents a profound disruption not only for spouses but also for children whose emotional, social, and developmental stability may be significantly affected. In Morocco, the Moroccan Family Code (Mudawwanat al-Usra) establishes a legal framework intended to safeguard the rights and welfare of children following the dissolution of marriage. Nevertheless, in judicial practice, the explicit integration of children’s rights within divorce judgments is not always consistently articulated, which may weaken the legal protection available to children after divorce. This study aims to analyze the legal protection of children’s rights in post-divorce proceedings under the Moroccan Family Code and to evaluate the role of family courts in ensuring the best interests of the child. The research employs a normative juridical approach, examining statutory provisions of the Moroccan Family Code, relevant legal doctrines, and conceptual frameworks related to child protection in Islamic family law. The findings indicate that although Moroccan legislation recognizes the principle of the best interests of the child, judicial decisions do not always explicitly formulate detailed provisions concerning children’s welfare, including maintenance, education, and emotional protection. As a result, certain aspects of children’s rights may remain insufficiently guaranteed in post-divorce situations. Strengthening judicial practice through the systematic inclusion of children’s rights in family court decisions is therefore essential. Such an approach would provide a clearer legal foundation for safeguarding children’s well-being, ensuring access to education, healthcare, and parental care, while minimizing the adverse consequences of parental conflict after divorce.